Urgensi Ekonomi Islam terhadap Fenomena Jual Beli Dalam Perspektif Al-Qur’an dan Hadis - Pase, Fahreza Akbar; Nasution, Yenni Samri Juliati (Ikatan Da'i Indonesia, 2023)
Buying and selling is also considered to have legal force between the two parties if an agreement has been reached on the price of the goods, even though the money has not been received. Because with an agreement, each party in it has obligations and rights that are mutually binding on one another, that means that a joint decision between the two parties has legal consequences of linking each other to carry out what has been agreed upon. If one of the parties tries to renege on the promise of what has been mutually agreed upon. Judging from the type of research, there is also the type of research used in this research, namely bibliography research or library research, which is research that is carried out by collecting information or making objective records that mean the object of research or collecting information that has the character of a bibliography, or analysis carried out to uncover a problem which is basically based on critical and in-depth analysis of relevant literature materials. This research results that the legal basis of buying and selling is mubah (permissible). However, when certain situations, conditions or circumstances are different, buying and selling can become mandatory and can also be illegal. Buying and selling becomes mandatory when there is an ihtikaf practice (hoarding of goods so that the stock disappears from the market and prices soar).